(untitled) (Journal of Student Affairs in Africa, 2021)
This paper offers a critical review of the adopted academic advising strategies at the Durban University of Technology. It is worth acknowledging that academic advising as a scholarly practice is in its developmental stage at South African tertiary institutions. The paper draws on the experiences of the authors as academic advisors to reflect on the strengths and challenges of the practices of academic advising. It interrogates and analyses the authors’ experiences vis-a-vis the extant literature on academic advising practices. In this way, the paper engages and advances best practices while simultaneously contributing to the body of literature on academic advising in South Africa.